2014
DOI: 10.1038/ncomms6318
|View full text |Cite
|
Sign up to set email alerts
|

The key role of transient receptor potential melastatin-2 channels in amyloid-β-induced neurovascular dysfunction

Abstract: Alzheimer’s dementia is a devastating and incurable disease afflicting over 35 million people worldwide. Amyloid-β (Aβ), a key pathogenic factor in this disease, has potent cerebrovascular effects that contribute to brain dysfunction underlying dementia by limiting the delivery of oxygen and glucose to the working brain. However, the downstream pathways responsible for the vascular alterations remain unclear. Here we report that the cerebrovascular dysfunction induced by Aβ is mediated by DNA damage caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
132
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 70 publications
(130 reference statements)
1
132
0
Order By: Relevance
“…This hypoactivity could be the result of A␤-derived disturbances in muscular function (Mukhamedyarov et al, 2014). Indeed, A␤ peptides are elevated in skeletal muscles of AD patients (Kuo et al, 2000), where they have been suggested to cause membrane depolarization in fibers by inhibiting the Na ϩ /K ϩ -ATPase and by forming membrane pores (Mukhamedyarov et al, 2011(Mukhamedyarov et al, , 2014. Moreover, A␤ oligomers have been detected in the muscle fibers of sporadic inclusion body myositis patients (Nogalska et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This hypoactivity could be the result of A␤-derived disturbances in muscular function (Mukhamedyarov et al, 2014). Indeed, A␤ peptides are elevated in skeletal muscles of AD patients (Kuo et al, 2000), where they have been suggested to cause membrane depolarization in fibers by inhibiting the Na ϩ /K ϩ -ATPase and by forming membrane pores (Mukhamedyarov et al, 2011(Mukhamedyarov et al, , 2014. Moreover, A␤ oligomers have been detected in the muscle fibers of sporadic inclusion body myositis patients (Nogalska et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, A␤ peptides are elevated in skeletal muscles of AD patients (Kuo et al, 2000), where they have been suggested to cause membrane depolarization in fibers by inhibiting the Na ϩ /K ϩ -ATPase and by forming membrane pores (Mukhamedyarov et al, 2011(Mukhamedyarov et al, , 2014. Moreover, A␤ oligomers have been detected in the muscle fibers of sporadic inclusion body myositis patients (Nogalska et al, 2010). TRPM2 expression in skeletal muscles is low (Fonfria et al, 2006a), which might explain the lack of improvement in AD-related hypoactivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations